Inteligencia emocional autopercibida y satisfacción del cliente en el Banco de Crédito del Perú filial Iquitos, 2023 - Almeida Amaral, Ana Andrea (2024)
In this research, we sought to specify how self-perceived emotional intelligence and customer satisfaction are related in a company in the financial sector of Loreto - Peru. The study design was non-experimental, crosssectional and descriptive-correlational in scope. A census was applied to fifteen service promoters (PDS) to diagnose their level of emotional intelligence and fifteen of their clients were surveyed to obtain an average of their perception of satisfaction with the service received by each PDS. The main hypothesis states that there is a positive relationship between both variables; which was tested through the Spearman coefficient, which yielded a value of 0.178, with which the main hypothesis was tested, concluding that there is a positive correlation, although of low intensity